Chapter Erranze poetiche e geografiche nei poeti del Gharb al-Andalus - Alves, Adalberto (Studi e saggi, 2021)
The arab poetry is born among the wandering bedouins of the desert. The long odes (qasidat), were born to be recited in the camp, at night, under the stars and around the fire. The ode includes always a section named nasib wich intention is to describe the erratic course of the desert rider in search of his beloved woman. On the other hand, throughout centuries and with rare exceptions, the social conditions of arab poets were precarious. This meant that they were obliged to wander between courts to find patrons, in order to guarantee means of subsistence. These two circumstances, together with the hazards of existing politics, determined the erring matrix of life of the ancient arab poets: most of them, despite their outstanding talent, were compelled to being mainly vagrant panegyrists.